2022
DOI: 10.1177/00108367221098488
|View full text |Cite
|
Sign up to set email alerts
|

Kraftwerk and the international ‘re-birth of Germany’: Multiplicity, identity and difference in music and International Relations

Abstract: Kraftwerk are widely recognised as one of the most important groups in the history of popular music – and for (West) German national identity in the 20th century. They have been labelled as both typically German and thoroughly cosmopolitan, but, rather than being paradoxical (as some have claimed), this tension reveals an under-explored international politics at work. Using the emerging approach of Multiplicity, I illuminate Kraftwerk’s international dimensions to develop the insight that all societies are int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…As a result, it is confirmed that Multiplicity 'involves a substantial expansion and potential diversification of the subject matter of IR, and one that opens it up further to continuous interaction with other disciplines'. 146 That underscores Multiplicity as a framework of analysis and, simultaneously, a bridge-builder for the fragmented IR with the re-defined subject matter. As Brieg Powel notes, the international is a part of 'an interconnected, multi-scalar social world that is shaped by multiplicity across all scales; multiplicity and relations permeate social scales.'…”
Section: Re-framing 'The International': Connections and Inequalitiesmentioning
confidence: 99%
“…As a result, it is confirmed that Multiplicity 'involves a substantial expansion and potential diversification of the subject matter of IR, and one that opens it up further to continuous interaction with other disciplines'. 146 That underscores Multiplicity as a framework of analysis and, simultaneously, a bridge-builder for the fragmented IR with the re-defined subject matter. As Brieg Powel notes, the international is a part of 'an interconnected, multi-scalar social world that is shaped by multiplicity across all scales; multiplicity and relations permeate social scales.'…”
Section: Re-framing 'The International': Connections and Inequalitiesmentioning
confidence: 99%